Clarifying mandates for marine ecosystem-based management. (16th November 2018) - Link, Jason S; Dickey-Collas, Mark; Rudd, Murray; McLaughlin, Richard; Macdonald, Nicol M; Thiele, Torsten; Ferretti, Johanna; Johannesen, Ellen; Rae, Margaret
Abstract: Mandates to execute ecosystem-based management exist but are not implemented sufficiently enough to reap the benefits of a growing blue economy.